Mobility and stability of large vacancy and vacancy-copper clusters in iron: An atomistic kinetic Monte Carlo study - Castin, N. (2012)
The formation of Cu-rich precipitates under irradiation is a major cause for changes in the mechanical response to load of reactor pressure vessel steels. In previous works, it has been shown that the mecha- nism under which precipitation occurs is governed by diffusion of vacancy-copper (VCu) complexes, also in the absence of irradiation. Coarse-grained computer models (such as object kinetic Monte Carlo) aimed at simulating irradiation processes in model alloys or steels should therefore explicitly include the mobil- ity of Cu precipitates, as a consequence of vacancy hops at their surface. For this purpose, in this work we calculate diffusion coefficients and lifetimes for a large variety of VCu complexes. We use an innovative atomistic model, where vacancy migration energies are calculated with little approximations, taking into account all effects of static relaxation and long-range chemical interaction as predicted by an interatomic potential. Our results show that, contrary to what intuition might suggest, saturation in vacancies tend toslow down the transport of Cu atoms.